PENGARUH KONSENTRASI KITOSAN DAN LAMA PENYIMPANAN TERHADAP TOTAL PLATE COUNT (TPC) BAKTERI PADA IKAN KEMBUNG (Rastrelliger sp.) ASIN - Ardhana Yulisma; Cut Yulvizar; Edi Rudi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
This research studied the application of chitosan on salted mackerel (Rastrelliger sp.) preservation during storage at room temperature. The research is aimed to study the effect chitosan concentration and storage time for Total Plate Count (TPC). The study was conducted in Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, Syiah Kuala University from April to August 2012. The research method was laboratory experimental.  The data was analyzed by Randomized Completely Design with two factorial. The first factor was chitosan concentration (three levels: 0%; 1%; 2%) while the second factor was storage time (four levels: 0; 2; 4; 8 weeks). The results of this study indicated that chitosan concentration was not significantly different for the Total Plate Count (p0,05), however storage time was significantly for the Total Plate Count (p0,05). Futhermore, the interaction chitosan concentration and storage time was significantly for the Total Plate Count (p0,05).